Qualitative Methods in IS/IT Research: Issues, Contributions and Challenges ? Forward - Bandara, Wasana; Fernandez, Walter; Rowlands, Bruce (Australasian Journal of Information Systems, 2012)
In this special issue, we adopt Van Maanen's (1979: 520) definition of qualitative research as an umbrella term to cover an “array of interpretive techniques that can describe, decode, translate, and otherwise come to terms with the meaning, not the frequency, of certain more or less naturally occurring phenomena in the social world”.